DSTYK Promotes Metastasis and Chemoresistance via EMT in Colorectal Cancer - Zhang, Jinyu; Miller, Zachary; Musich, Phillip R.; Thomas, Ashlin E.; Yao, Zhi Q.; Xie, Qian; Howe, Philip H.; Jiang, Yong (Frontiers in Pharmacology, 2020)
Objective Tumor metastasis and resistance to chemotherapy are two critical factors that contribute to the high death rate of colorectal cancer (CRC) patients. Metastasis is facilitated by the epithelial-mesenchymal transition (EMT) of tumor cells, which has emerged not only as a fundamental process during metastasis, but is also a key process leading to chemoresistance of cancer cells. However, the underlying mechanisms of EMT in CRC cell remain unknown. Here, we aim to assess the role of dual serine/threonine and tyrosine protein kinase (DSTYK) in CRC metastasis and chemoresistance. Methods To study the role of DSTYK in TGF-β-induced EMT, we employed techniques including Crispr/Cas9 knockout (KO) to generate DSTYK KO cell lines, RT-PCR to detect the mRNA expression, immunofluorescence analyses, and western blots to detect protein levels of DSTYK in the following 4 cell lines: control LS411N-TβRII and LS411N-TβRII/DSTYK KO, control LS513 and LS513/DSTYK KO cells, treated with/without TGF-β. The effects of DSTYK on apoptosis were investigated by MTT assays, flow cytometry assays, and TUNEL assays. The expression of DSTYK in CRC patients and its correlation with EMT markers were determined by bioinformatics analysis. For in vivo analysis, both xenograft and orthotopic tumor mouse models were employed to investigate the function of DSTYK in chemoresistance and metastasis of tumors. Results In this study, we demonstrate that the novel kinase DSTYK promotes both TGF-β-induced EMT and the subsequent chemoresistance in CRC cells. DSTYK KO significantly attenuates TGF-β–induced EMT and chemoresistance in CRC cells. According to the Gene Expression Omnibus (GEO) database, the expression of DSTYK is not only positively correlated to the expression of TGF-β, but proportional to the death rate of CRC patients as well. Evidently, the expression of DSTYK in the metastatic colorectal cancer samples from patients was significantly higher than that of primary colorectal cancer samples. Further, we demonstrate in mouse models that chemotherapeutic drug treatment suppresses the growth of DSTYK KO tumors more effectively than control tumors. Conclusion Our findings identify DSTYK as a novel protein kinase in regulating TGF-β–mediated EMT and chemoresistance in CRC cells, which defines DSTYK as a potential therapeutic target for CRC therapy.